A Low-Cost, DIY Ultrasonic Water Level Sensor for Education, Citizen Science, and Research - Philip Bresnahan; Ellen Briggs; Benjamin Davis; Angelica Rodriguez; Luke Edwards; Cheryl Peach; Nan Renner; Harry Helling; Mark Merrifield (Oceanography, 2023)
A low-cost (~$100), do-it-yourself (DIY) ultrasonic water level sensor/datalogger has been designed, constructed, and tested for use in education, citizen/community science, and research settings. The sensor package comprises an ultrasonic distance sensor, a microcontroller running Arduino firmware, a micro-SD card for datalogging, a real-time clock for timekeeping and sleep functions, and an OLED screen for real-time display. Electronics are housed in low-cost custom containers using either upcycled plastic containers or laser-cut acrylic. Reported ultrasonic sensor accuracy is 5 cm across a range of 15–645 cm, with an estimated power budget of 76 days of operation on a rechargeable 10 amp-hr battery. The DIY sensor has been field tested alongside two commercial sensors for 18 days in Wilmington, North Carolina, including during Tropical Storm Colin, with all sensor measurements in close agreement (e.g., root mean squared error of 1.5 cm between the DIY sensor and a proven commercial unit). Potential applications, design and construction, and deployment recommendations for the sensors are described, as well as simple and inexpensive modifications to the sensor and its packaging that could further improve performance. Preliminary lesson plans written to accompany the device for high school- and undergraduate-level educational projects are available.